Twinning behavior in a rolled Mg-Al-Zn alloy under dynamic impact loading. (June 2018) - Mao, Longhui; Liu, Chuming; Chen, Tao; Gao, Yonghao; Jiang, Shunong; Wang, Renke
Abstract: Twinning-stress correlation of a basal textured Mg-Al-Zn alloy was studied after impact test. The deformed microstructure was characterized using electron backscattered diffraction (EBSD) while the stress analysis during impact process was modeled by finite element method. Results showed that both the tension and compression region of the sample were dominated by high density deformation twins. Various twinning modes and variant selections were determined by trace method and misorientation analysis. Preliminary analysis suggested that some rare twinning modes such as { 10 1 ¯ 1 }-{ 10 1 ¯ 1 } and { 10 1 ¯ 2 }-{ 10 1 ¯ 2 } double twinning likely occurred after deformation. Graphical abstract: Unlabelled Image